GIADA – Grain Impact Analyzer and Dust Accumulator – Onboard Rosetta spacecraft: Extended calibrations. (September 2016) - Della Corte, V.; Sordini, R.; Accolla, M.; Ferrari, M.; Ivanovski, S.; Rotundi, A.; Rietmeijer, F.J.M.; Fulle, M.; Mazzotta-Epifani, E.; Palumbo, P.; Colangeli, L.; Lopez-Moreno, J.J.; et al.
Abstract: Despite a long tradition of dust instruments flown on-board space mission, the largest number of these can be considered unique as they used different detection techniques. GIADA (Grain Impact Analyzer and Dust Accumulator), is one of the dust instruments on-board the Rosetta spacecraft and is devoted to measure the dust dynamical parameters in the coma of comet 67P/Churyumov–Gerasimenko. It couples two different techniques to measure the mass and speed of individual dust particles. We report here the results of an extended calibration activity carried-out, during the hibernation phase of the Rosetta mission, on the GIADA Proto Flight Model (PFM) operative in a clean room in our laboratory. The main aims of an additional calibration campaign are: to verify the algorithms and procedures for data calibration developed before Rosetta launch; to improve the comprehension of GIADA response after the increased knowledge on cometary dust, e.g. the composition of dust particles after Stardust mission. These calibration improvements implied a final step, which consisted in defining transfer functions to correlate the new calibration curves obtained for the GIADA PFM to those to be used for GIADA onboard the Rosetta spacecraft. The extended calibration activity allowed us to analyze GIADA data acquired in the 67P/C–G coma permitting to infer additional information on cometary dust particles, e.g. density and tensile strength. Abstract : Highlights: GIADA in situ dust instrument on board the Rosetta spacecraft. Extended calibration activity on the GIADA Proto Flight Model (PFM). Improve the comprehension of GIADA responses vs. knowledge on cometary dust. Definition of instrument transfer functions to obtain the physical measurements. Calibrations allowed us to infer cometary dust particles additional properties.